2007
DOI: 10.1038/ja.2007.24
|View full text |Cite
|
Sign up to set email alerts
|

Nigerasperones A~C, New Monomeric and Dimeric Naphtho-γ-pyrones from a Marine Alga-derived Endophytic Fungus Aspergillus niger EN-13

Abstract: Three new naphtho-g-pyrones, 5-hydroxy-6,8-dimethoxy-2-hydroxymethyl-4H-naphtho [2,3-b]pyran-4-one (1, nigerasperone A), 3,3Ј-dihydro-2,2Ј,5,5Ј-tetrahydroxy-8,8Ј,10,10Ј-tetramethoxy-2,2Ј-dimethyl-(6Ј,9-bi-4H-naphtho[1,2-b]pyran)-4,4Ј-dione (2, nigerasperone B), and 3Ј-hydro-2Ј,5,5Ј,8-tetrahydroxy-6,6Ј,8Ј-trimethoxy-2,2Ј-dimethyl-(7,10Ј-bi-4H-naphtho[2,3-b]pyran)-4,4Ј-dione (3, nigerasperone C), together with nine related known compounds were characterized from Aspergillus niger EN-13, an endophytic fungus isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…In the past years, a number of new metabolites have been isolated and identified and their biological activities have been evaluated [24]. As part of our recently initiated program to assess the chemical and biological diversity of endophytic fungi derived from marine algae [512], Penicillium chrysogenum QEN-24S, an endophytic fungus obtained from the inner tissue of an unidentified marine red algal species of the genus Laurencia , attracted our attention. This fungus displayed inhibitory activity against the growth of pathogenic fungus Alternaria brassicae in our initial dual culture test (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, a number of new metabolites have been isolated and identified and their biological activities have been evaluated [24]. As part of our recently initiated program to assess the chemical and biological diversity of endophytic fungi derived from marine algae [512], Penicillium chrysogenum QEN-24S, an endophytic fungus obtained from the inner tissue of an unidentified marine red algal species of the genus Laurencia , attracted our attention. This fungus displayed inhibitory activity against the growth of pathogenic fungus Alternaria brassicae in our initial dual culture test (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C NMR and HSQC spectra revealed that compound 1 contained 34 carbons, including two methyl groups, four methoxy groups, one sp 3 methine, one sp 3 methylene, six sp 2 methines, 20 quaternary sp 2 carbons, with two being conjugated carbonyls. The above evidences were indicative of a dimer consisting of two linear naphtho-g-pyrone monomers (Akiyama et al 2003;Zhang et al 2007).…”
Section: Resultsmentioning
confidence: 95%
“…[32]. A new naphthoquinoneimine derivative, 5,7-dihydroxy-2-[1-(4-methoxy-6-oxo-6H-pyran-2-yl)-2-phenylethylamino]-[1,4]-naphthoquinone ( 30 ), and asperamides A ( 31 ), nigerasperone C ( 32 ) from the marine brown alga Colpomenia sinuosa- derived endophytic fungus Aspergillus niger EN-13 displayed moderate activity against Candida albicans [3335]. Chaetopyranin ( 33 ) isolated from Chaetomium globosum , an endophytic fungus derived from the marine red alga Polysiphonia urceolata , exhibited moderate to weak cytotoxic activity [36].…”
Section: Biological Activity and Pharmaceutical Metabolites Of Marmentioning
confidence: 99%